Plant Life of Southwestern Australia. Adaptations for Survival - Groom, Philip (De Gruyter, 2015)
Southwestern Australia is unique as it contains the world`s most nutrient-impoverished soils, experiences a prolonged-summer period and the vegetation is extremely fire-prone. It is also world-renowned for its relative high level of flora biodiversity. This book focuses on the diverse range of morphological and physiological adaptations evolved by the flora to survive in the harsh Mediterranean-type climate.